Hypoglycemic effect of peony flowers polyphenols based on gut microbiota and metabolomics - Chen, Ling; Wang, Xuefang; Ning, Erjuan; Zhang, Lipan; Li, Feifei; Wang, Lupeng; Zhu, Jie; Zhang, Huanan; Wang, Tao; Ma, Yanni; Wang, Wei; Li, Xiao (Frontiers in Nutrition, 2025)
IntroductionType 2 diabetes mellitus (T2DM), remains a significant global public health concern. Peony has a long history of consumption and medicinal in China, and is rich in polyphenols, flavonoids, polysaccharides, and other components. However, the hypoglycemic activity and underlying mechanism of action of peony flowers polyphenols (PP) remain nebulous. Therefore, we investigate the hypoglycemic effect and mechanism of action of PP on T2DM mice.MethodsPP was extracted and isolated from peony flowers (Paeonia ostii “Fengdan”), the total polyphenol content (TPC) in PP was determined by the Folin-Ciocalteu method and the contents of 17 components in PP were determined by high-performance liquid chromatography. The high-fat diet (HFD) combined with streptozotocin (STZ) was used to establish T2DM mouse model, and the hypoglycemic effect and mechanism of PP based on gut microbiota and metabolomics were investigated.ResultsThe TPC in PP was 81.13 ± 2.89%. The results showed that after 8 weeks of intragastric administration, PP significantly reduced the fasting blood glucose (FBG) (P < 0.05), serum insulin level (P < 0.05), and insulin resistance index (P < 0.05), improved impaired glucose tolerance, regulated serum liver and kidney function related indicators, significantly increased superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) levels (P < 0.05), significantly decreased malondialdehyde (MDA) level (P < 0.05) in the liver, and increased the contents of short-chain fatty acids (SCFAs) in the gut of T2DM mice. The results of 16S rRNA sequencing showed that PP could alter the gut microbiota of T2DM mice, increase the relative abundance of Firmicutes and Bacteroidota, while decrease the relative abundance of Proteobacteria. Non-targeted metabolomics results showed that the high-dose group of PP (PPH) can reverse the metabolic disorders of metabolite markers induced by T2DM in vivo.ConclusionsConsequently, PP may play a hypoglycemic role by regulating intestinal flora and amino acid metabolism pathway. The research establishes a foundation for using PP as a functional food to prevent or alleviate type 2 diabetes mellitus.